Kurikulum PAI untuk Madrasah Ibtidaiyah: Konsep, Aplikasi dan Pengembangannya - Arifa Marlianti; Dara Afria Nur Afnia; Dinda Aurelia (Tarbiyah : Jurnal Ilmu Pendidikan dan Pengajaran, 2025)
This study aims to describe the concept, implementation, and development of the Islamic Education Curriculum (PAI) in Madrasah Ibtidaiyah. The PAI curriculum plays a crucial role in shaping students with strong faith, noble character, and the ability to practice Islamic values in daily life. This research employs a library research method, collecting data from digital books, ebooks, and relevant scholarly sources. The findings indicate that the PAI curriculum covers essential values such as tauhid, worship, morals, and social interactions, which are integrated into the learning process. Its implementation includes planning, classroom activities, religious habituation, and comprehensive evaluation encompassing cognitive, affective, and psychomotor aspects. Curriculum development requires relevance, contextualization, and technological integration to meet contemporary educational demands.